Systematic Literature Review: Strategi Pembelajaran Individual pada Peserta Didik - Harjun; Priska Prasilia; Nur Dalilah Ariandi Zahira; Lulu Ikfha; Rasmiati; Ummirah Madany; WD. Anadine Arsyamecka Abdullah; Atika Sari Maisura; Nursyafika; Findi Yusari; Alifkha Della Az Zahra; Muh. Alfiansyah Toroda (Indo Publishing, 2025)
The individual learning strategy is an approach that places students at the center of the learning process by considering their unique abilities, interests, and needs. However, learning practices in Indonesia remain largely uniform and have not fully embodied the principles of Freedom to Learn, which emphasize independence, flexibility, and recognition of diverse learning styles. This study aims to analyze the effectiveness of individual learning strategies in improving students’ learning outcomes, motivation, and independence through a Systematic Literature Review (SLR) approach. The review was conducted in three main stages planning, implementation, and reporting by examining 20 scientific articles published between 2017 and 2025 from reputable databases such as GARUDA, SINTA, and Google Scholar. The findings indicate that individual learning strategies are effectively implemented in both general and inclusive education settings, as they allow adjustments to learning goals, methods, and materials based on students’ characteristics. This approach also supports the realization of adaptive, student-centered, and flexible learning aligned with the spirit of Merdeka Belajar. Nevertheless, several challenges remain, including limited resources, time constraints, and teachers’ pedagogical readiness. Therefore, professional development, teacher training, and the integration of educational technology are essential to optimize its implementation. The results of this study are expected to provide practical insights for educators in designing inclusive, innovative, and learner-oriented instructional practices that reflect the values of Merdeka Belajar in modern education.